Static lateral load capacity of extruded wood-plastic composite-to-metal single-bolt connections, considering failure at the ends - Chen, Chen; Kuang, Fuchun; Tor, Onder; Quin, Franklin; Xiong, Zhengwei; Zhang, Jilei (BioResources, 2019)
The effect of the end distance was studied relative to the static ultimate lateral load capacity of a single-shear unconstrained wood-plastic-composite-to-metal single-bolt connection (SUWSC). Equations estimated the static ultimate lateral loads of the SUWSCs that failed during the end tear-out, splitting, and yield modes and were obtained using stress concentration factor regression- and mechanics-based approaches. The experimental results showed that the stress concentration factor was a linear function of the end-distance to bolt-diameter ratio for the SUWSCs that failed during end tear-out and splitting modes. The static ultimate lateral loads of the SUWSCs that failed during the yield modes were estimated using a mechanics-based equation. The minimum end distance for the SUWSCs that failed without end fracture (i.e., only with yield mode) was 25.4 mm, which was four times larger than the bolt diameter.